The removal and burning of pineapple residue in pineapple cultivation on tropical peat: An economic viability comparison - Ahmed, Osumanu Haruna; Mohd Hanif, Ahmad Husni; Abd. Ghani, Awang Noor; Musa, Mohamed Hanafi (Universiti Putra Malaysia Press, 2002)
The study was conducted to compare the benefits and costs of in situ burning of pineapple residues with removal of pineapple residues (before replanting) in pineapple cultivation on tropical peat. Treatments used were: (i) residues (leaves, crowns, and peduncles) removal followed by fertilization (REF) and (ii) residues (leaves, crowns, and peduncles) burnt followed by fertilization (usual practice) (REF). At the end of the study, the average fruit weight per treatment was recorded. Fruit weight multiplied by the plant density of 56,250 will give the total yield per hectare. The product of the total yield/ha and farm-gate price will give the gross revenue of crop production. Cost of labour was based on the wage system practiced by the pineapple estates. Farm-gate market prices were used for assessing farm materials and other inputs. Cost of land was based on the annual rental value for pineapple plantations. An interest rate of 12% was charged on the capital used. Under the Environmental Quality Act, 1978 amended in 1998, and according to the Air Pollutant Index (API) the polluters have to pay the principal fine imposed for polluting the air through open burning ofpineapple residues. All these costs will be taken into account when calculating the production cost ofpineapple. Burning did not significantly increase yield. Cost and benefit analysis revealed that removal ofpineapple residues (RRF) is more economically viable than burning the residues (REF). Adoption ofRRF requires further studies in selecting the most suitable method of enhancing the quality of the environment or developing product(s) of commercial value from pineapple residues. The cost of the study should be bome partly by the government, the pineapple estates, and the public.